Kupffer Cells as a Target for Immunotherapy - Takashi Sakai; Wen-Ling Lin (J, 2022)
Kupffer cells (KCs) are resident macrophages in the liver. Recent studies have revealed that KCs are closely related to inflammatory liver diseases, including nonalcoholic liver diseases (NAFLD). From this point of view, KC transplantation can be a candidate for immunotherapy against inflammatory diseases. Similar to general macrophages, KCs show several different phenotypes according to their environment. Activated KCs are involved in either proinflammatory responses or anti-inflammatory responses. Thus, to manipulate KCs for immunotherapy, it is crucial to control the direction of KC activation. Here, we summarize the outlook and the issues hindering immunotherapy using KC transplantation.